Critical theory from Adorno to Habermas - Talledo, Tomasito T. (Danyag :the UPV journal of humanities and social sciences)
"The members of the Frankfurt School worked out independently of each other the theoretical inheritance they received from the Western tradition of critique as shaped by the historical demands of their milieu. the kernel ideas of the members' significant works constitute the problematic of what is now called critique of ideology. This paper points out its limitations as a tool sociological analysis."